(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Allergic conjunctivitis (AC), defined by ocular itching, hyperemia, lacrimation and edema, impairs the quality of life across the globe. Ebastine is available as an oral antihistamine formula, such as tablets and syrup, for allergic disorders. Topical antihistamines are preferred over oral agents since their direct application at the site of action results in rapid onset and superior efficacy with less systemic side effects. The objective of the present work was to evaluate the antiallergic potential of optimized ebastine (1% w/v) colloidal ocular formulation by performing in vitro study like hen's egg chorioallantoic membrane test (HET-CAM) for tolerability and in vivo efficacy study in ovalbumin (OA)-induced allergic conjunctivitis (AC) with acute ocular irritation study. Eye scratching behavior and edema were evaluated after topical antigen challenge. Edema was scored at periodic interval after the instillation of ovalbumin followed by histopathology. The results showed that ebastine (1% w/v) colloidal ocular formulation was effective in inhibiting symptoms of eye inflammation induced by ovalbumin. Further, the study indicated that said formulation has a quick onset and the duration of effect sufficient to provide relief from symptoms for 24 hr. Ocular irritation by HET-CAM assay showed that the developed formulation does not cause any irritation to the blood vessels. Acute ocular irritation test was performed using rabbits and results showed that developed formulation was non-irritant to the eye. The present study revealed that the ocular ebastine formulation could offer a novel therapeutic opportunity against IgE-mediated allergic conjunctivitis.